Compensation method of the machine tool spindle thermal displacement for accurate monitoring of cutting forces - Sarhan, Ahmed AD; Matsubara, Atsushi (2011)
In this research work, the authors use displacement sensors in the spindle structure to monitor cutting forces for intelligent machining. However, the monitoring quality in the long term is a problem because sensor signals involve offset drift, which is mainly attributable to the thermal displacement of the spindle. To solve this problem, we attached thermal sensors in the machine and cooling system. The estimation of the spindle thermal displacement based on temperature data from these thermal sensors can provide more information for monitoring of cutting forces. For accurate monitoring of cutting forces, thermal displacement compensation scheme is proposed, and the monitoring tests of cutting forces in end milling operations are carried out as cases study. With thermal displacement compensation scheme implemented, the experimental result shows that the monitoring of small and medium scale cutting forces is possible, if cutting process is intermittent.